Prevalence of undiagnosed hypertension and associated factors among adults in Durame town, Southern Ethiopia: a cross-sectional study - Suliman, Abebe; Tadesse, Sebsibe; Abute, Lonsako; Selamu, Markos (Frontiers in Epidemiology, 2023)
Background: Undiagnosed hypertension is a major public health problem causing severe cardiovascular disorders that are responsible for a high proportion of morbidities and mortalities, especially among adults living in low-income countries. However, there is a paucity of information that describes its epidemiology in Ethiopia. This study aimed to assess the prevalence of undiagnosed hypertension and associated factors among adults in Durame town, southern Ethiopia. Methods: A community-based cross-sectional study was conducted from July to September 2022. Data were collected from 526 randomly selected adults aged ≥18 years using a pre-tested questionnaire. The binary logistic regression models were used to identify factors associated with undiagnosed hypertension. Results: The prevalence of undiagnosed hypertension among adults in Durame town, southern Ethiopia, was found to be 14.0% (95% CI: 11.2–17.1). Family history of hypertension [AOR = 6.9, 95% CI: (3.62, 13.27)], drinking too much alcohol [AOR = 5.7, 95% CI: (2.97, 10.75)], physical inactivity [AOR = 2.5, 95% CI: (1.34, 4.73)], consuming street foods regularly [AOR = 2.8, 95% CI: (1.28, 6.01)], and seeking healthcare for hypertensive symptoms without serious illness [AOR = 2.4, 95% CI: (1.28, 4.56)] were significantly associated with developing undiagnosed hypertension. Conclusion: The study has revealed that one in seven adults had undiagnosed hypertension in the study area. Thus, interventions to prevent hypertension should target increasing awareness among people with a family history of hypertension, controlling excessive alcohol consumption, promoting physical exercise, regulating street food markets, and improving the health-seeking behavior of adults in urban settings.